MEMBANGUN PERADABAN DUNIA YANG DAMAI: PENTINGNYA PEMBAHARUAN ISLAM DAN “KEARIFAN” BARAT (Tinjauan Buku “Masa Depan Islam” Karya John L. Esposito) - Asep Saefullah (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2012)
The Islamic transformation should have not occurred if it remained consistency with its assessment. Any movements or groups of extremist, terrorist, fundamentalist, radical, or whatever its name is considered a hard act towards its teachings and implementations, must be separated from the mainstream Muslims and should be seen throughout their contexts. It should also be understood as the teaching of Islam and Islam as practiced. The capital pluralism should be used as a basis for strengthening the unity and integrity, not seen as barriers. Muslims are in need of conflict management to resolve issues that are faced by the Muslims.